2020
DOI: 10.1186/s12711-020-00566-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of genomic breeding values based on pre-selected SNPs using ssGBLUP, WssGBLUP and BayesB for Edwardsiellosis resistance in Japanese flounder

Abstract: Background: Edwardsiella tarda causes acute symptoms with ascites in Japanese flounder (Paralichthys olivaceus) and is a major problem for China's aquaculture sector. Genomic selection (GS) has been widely adopted in breeding industries because it shortens generation intervals and results in the selection of individuals that have great breeding potential with high accuracy. Based on an artificial challenge test and re-sequenced data of 1099 flounders, the aims of this study were to estimate the genetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
(77 reference statements)
0
21
1
1
Order By: Relevance
“…In this respect, Teissier et al [35] concluded that for polygenic traits, the same accuracy could be obtained with the ssGBLUP and WssGBLUP method, which is in complete agreement with the findings of our study. Recently, Lu et al [45] indicated that WssGBLUP was more accurate (6%) than ssGBLUP for Edwardsiellosis resistance in Japanese flounder, which may be due to the presence of QTL on chromosome 14 with large effects for this trait.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Teissier et al [35] concluded that for polygenic traits, the same accuracy could be obtained with the ssGBLUP and WssGBLUP method, which is in complete agreement with the findings of our study. Recently, Lu et al [45] indicated that WssGBLUP was more accurate (6%) than ssGBLUP for Edwardsiellosis resistance in Japanese flounder, which may be due to the presence of QTL on chromosome 14 with large effects for this trait.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the inclusion of most of the causal mutations, and decreased limitation due to linkage between SNPs and causal mutations, the use of whole-genome resequencing (WGS) could increase predictive ability. However, empirical results comparing the use of WGS vs a set of SNPs show nil to marginal increase in genomic prediction accuracy ( Lu et al 2020 ; Yoshida and Yáñez 2021 ). This suggests WGS is unnecessary for this purpose and supports our suggestion that reduced genome representation provides accurate genomic prediction estimates to assist in the selection of elite broodstock lines.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the inclusion of most of the causal mutations, and decreased limitation due to linkage between SNPs and causal mutations, the use of whole genome resequencing (WGS) could increase predictive ability. However, empirical results comparing the use of WGS versus a set of SNPs show nil to marginal increase in genomic prediction accuracy (Lu et al . 2020; Yoshida and Yáñez 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the inclusion of most of the causal mutations, and decreased limitation due to linkage between SNPs and causal mutations, the use of whole genome resequencing (WGS) could increase predictive ability. However, empirical results comparing the use of WGS versus a set of SNPs show nil to marginal increase in genomic prediction accuracy (Lu et al 2020;Yoshida and Yáñez 2021). This suggests WGS is unnecessary for this purpose and supports our suggestion that reduced genome representation provides accurate genomic prediction estimates to assist in the selection of elite broodstock lines.…”
Section: Applied Relevance Of Genomic Prediction Of Growthmentioning
confidence: 99%